2023
DOI: 10.14202/vetworld.2023.1266-1276
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in veterinary medicine: A literature review

Abstract: Veterinarians are commonly exposed to occupational stressors, including excessive workload and financial constraints. These stressors can lead to psychological distress, which typically results in mental health disorders such as depression, anxiety, and burnout and can even culminate in suicide attempts or suicide deaths. Risk factors associated with poor mental health and high rates of suicide in veterinary practitioners include continuous exposure to challenging scenarios, such as interpersonal conflicts, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Veterinarians show higher levels of stress ( 2–5 ), burnout ( 2 , 6 ), depression ( 2 , 3 , 7 ), and suicidality ( 2 , 3 , 5 , 7–9 ) than the general population and other occupational groups. Risk factors associated with poor mental health and high suicide rates among veterinarians include constant exposure to difficult scenarios such as interpersonal conflict, the performance of euthanasia and easy access to lethal suicide drugs such as opioids and anesthetics, highlighting the need to better understand predisposing factors and improve mental health in this professional environment, as well as introduce primary mental health care interventions ( 10 ). In an American study, Volk et al ( 11 ) reported a lower level of well-being among veterinarians compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Veterinarians show higher levels of stress ( 2–5 ), burnout ( 2 , 6 ), depression ( 2 , 3 , 7 ), and suicidality ( 2 , 3 , 5 , 7–9 ) than the general population and other occupational groups. Risk factors associated with poor mental health and high suicide rates among veterinarians include constant exposure to difficult scenarios such as interpersonal conflict, the performance of euthanasia and easy access to lethal suicide drugs such as opioids and anesthetics, highlighting the need to better understand predisposing factors and improve mental health in this professional environment, as well as introduce primary mental health care interventions ( 10 ). In an American study, Volk et al ( 11 ) reported a lower level of well-being among veterinarians compared to the general population.…”
Section: Introductionmentioning
confidence: 99%